2014
DOI: 10.1016/j.rasd.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Intact hedonic responses to sweet tastes in autism spectrum disorder

Abstract: The Sweet Taste Test (STT) is a standardized measure designed to index the ability to detect differences in sweet tastes (sweet taste sensitivity) and hedonic responses to sweet tastes (sweet taste liking). Profiles of response on the STT suggest enhanced hedonic responses to sweet tastes in psychiatric disorders characterized by dysfunctional reward processing systems, including binge-eating disorders and substance use disorders, and a putative mechanism governing STT responses is the brain opioid system. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…Common factors for food refusal that are greater in children with ASD compared with TD include texture/consistency, taste/smell, mixtures, brand, and shape (Hubbard et al, 2014). Using the sweet taste test, Damiano and colleagues found that individuals with ASD show the same sensitivity and pleasurable effects of sweet taste as individuals with TD, suggesting that taste aversions may be specific to certain kinds of flavors as opposed to overall gustatory function (Damiano et al, 2014). In the olfactory domain, individuals with ASD rate odors as less pleasant compared with individuals with TD (Hrdlicka et al, 2011).…”
Section: Atypical Sensory Processing In Asdmentioning
confidence: 99%
“…Common factors for food refusal that are greater in children with ASD compared with TD include texture/consistency, taste/smell, mixtures, brand, and shape (Hubbard et al, 2014). Using the sweet taste test, Damiano and colleagues found that individuals with ASD show the same sensitivity and pleasurable effects of sweet taste as individuals with TD, suggesting that taste aversions may be specific to certain kinds of flavors as opposed to overall gustatory function (Damiano et al, 2014). In the olfactory domain, individuals with ASD rate odors as less pleasant compared with individuals with TD (Hrdlicka et al, 2011).…”
Section: Atypical Sensory Processing In Asdmentioning
confidence: 99%
“…Clinical data relative to other (non‐social) rewarding stimuli appear less consistent. Concerning primary rewards, individuals with ASD were reported to display intact hedonic responses to sweet taste (Damiano et al , ) and stronger activation in brain reward regions (NAc, orbitofrontal cortex, amygdala and insula) in response to food cues (Cascio et al , ) pointing to increased food reward in these patients. In line with this, children with ASD were shown as less able to delay gratification when tested for a food reward (Faja and Dawson, ).…”
Section: Evidence For Blunted Reward Processes In Autism Spectrum Dismentioning
confidence: 99%
“…Interestingly, attempts to translate the animal findings of stress-induced anhedonia to humans have largely resulted in negative results. For example, patients with MDD, schizophrenia, or autism do not show deficits in the hedonic response to sucrose compared to healthy controls (Berlin et al , 1998; Damiano et al , 2014; Dichter et al , 2010). These results from human and animal studies suggest that either: a) the sucrose preference test is not a valid assessment of pleasure; or b) psychiatric disorders such as MDD, schizophrenia, and autism are not associated with deficits in pleasure.…”
Section: Translational Assessments Of Reward and Motivationmentioning
confidence: 99%
“…For example, although deficits in motivation were recognized nearly a century ago in schizophrenia (Kraepelin, 1921), recent evidence suggests that such deficits are dissociable from consummatory pleasure, which is intact in individuals with schizophrenia (Barch et al , 2015; Gard et al , 2007; Heerey et al , 2007). Additionally, autism spectrum disorder is associated with anhedonia relating to social, but not other, stimuli (Chevallier et al , 2012; Damiano et al , 2014), but motivation to complete certain tasks can be greater in autism spectrum disorder compared to healthy controls (Damiano et al , 2012). …”
Section: Translational Assessments Of Reward and Motivationmentioning
confidence: 99%